2015
DOI: 10.1007/s13178-015-0200-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Concurrent Sex Partnerships and Social Norms: Young Adults’ Sexual Relationships in the Metropolitan Communities of Cape Town, South Africa

Abstract: Even though antiretroviral treatment is becoming more efficient and available, new HIV infections still occur, and this is particularly evident in the sub-Saharan Africa region. Heterosexual intercourse is still the main mode of HIV transmission in the region, and multiple and concurrent sex partners are arguably crucial for the spread of the epidemic. It is therefore problematic that sexual risk-taking, in terms of multiple and concurrent sex partners, persists in spite of HIV awareness and knowledge. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…While, authors indicated male-headed households in urban areas were more likely to be food secure than female-headed households, both male-and female-headed households are more prone to experience food insecurity in rural areas. Considering most Africans in rural areas are involved in the agricultural sector, it is likely they have experienced hunger at some point in their lives (Tibesigwa &Visser, 2015). In the KwaZulu Natal province of South Africa, an estimated 20% of the households are involved in agricultural activities as additional sources of income and food.…”
Section: Introductionmentioning
confidence: 99%
“…While, authors indicated male-headed households in urban areas were more likely to be food secure than female-headed households, both male-and female-headed households are more prone to experience food insecurity in rural areas. Considering most Africans in rural areas are involved in the agricultural sector, it is likely they have experienced hunger at some point in their lives (Tibesigwa &Visser, 2015). In the KwaZulu Natal province of South Africa, an estimated 20% of the households are involved in agricultural activities as additional sources of income and food.…”
Section: Introductionmentioning
confidence: 99%
“…The informal settlements of Kampala are a closed community, with a high likelihood of the dwellers, including young psychoactive-substance-users engaging in unsafe multiple sexual relationships with sex workers, and HIV-infected individuals within their circles [16,28]. Unprotected sexual intercourse increases opportunities for transmission of STIs [13,[29][30][31][32]. Despite these risk factors, little is known about the magnitude and factors associated with multiple sexual partnerships among young psychoactive users.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the research examining the psychosocial determinants of risky sexual practices includes socio-contextual sexual practices, such as age-discrepant partners whereby young girls engage in sex with men who are much older than them, and more recently multiple concurrent sexual partnerships (Adimora, Schoenbach, & Doherty, 2007; Epstein & Morris, 2011; Evans et al, 2016; Mah & Halperin, 2010; Tibesigwa & Visser, 2015). These factors show an association with HIV infection rates and researchers agree that this relationship does not infer causality.…”
mentioning
confidence: 99%